Puerperium Stroke and Subsequent Tissue-Type Plasminogen Activator–Induced Hemorrhage: A Case Report. Issue 5 (May 2021) - Hanson, Ryan; Brown, Peter; Temple-Cooper, Mary; Hoyt, McCallum
Abstract : We report a case of ischemic stroke in an apparently healthy 35-year-old gravida 2 para 1 who was treated with tissue-type plasminogen activator (tPA) 9 hours after vaginal delivery that resulted in severe hemorrhage. Limited data suggest use of thrombolytics in pregnancy is safe, but there is a paucity of evidence assessing their use immediately postpartum. We describe successful combination of tPA with endovascular mechanical thrombectomy (EMT) for treatment of postpartum stroke, which was followed by extensive uterine bleeding.